Effect of compression on the global optimization of atomic clusters - Doye, J (American Inst of Physics, 2000)
The optimization of atomic clusters by transformation of potential energy was discussed. The method showed the reduction of transition states on potential energy surfaces (PES). The Lennard-Jones clusters were optimized by a double funnel topography. The stationary points were reduced on PES in the first transformation and in the second transformation, Hopping algorithms were used to become PES increasingly dominant.